Game Design and Affect: How Games Move Us as a Catalyst for Explorations in Game Studies - Hugelmann, Christopher (Loading, 2019)
How Games Move Us: Emotion By Design is an introduction to the ways in which digital games and game studies are slowly encroaching on other territory; in this case, Isbister looks at the intersection of psychology, kinesthetics, design and games and how new notions from these fields alter our understanding of games as a whole. The book is aimed at changing how people talk about and understand digital games, not only as a technical object but as a social medium. Isbister readily accomplishes her goal of highlighting the ways that people can affect and are affected by games, though at times, the book struggles with its strong reliance on examples and dated references to the field of game studies and psychology.